PERBEDAAN HASIL BELAJAR GEOMETRI SISWA MENGGUNAKAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUAN GEOGEBRA, MODEL KOOPERATIF TIPE GROUP INVESTIGATION, DAN MODEL DIRECT INSTRUCTION - Virginia Polii; James U. L. Mangobi; Derel F. Kaunang (Discovery : Jurnal Ilmu Pengetahuan, 2022)
This research was carried out at SMA Negeri 1 Dumoga in the second semester of the 2020/2021 academic year. The research method used is quasi-experimental. The research subjects were 23 students of class X MIA 1 who were taught using the Cooperative learning model of Group Investigation tipe, 23 students of class X MIA 2 who were taught using the Direct Instruction learning model, and 24 students of class X MIA 3 who were taught using the Geogebra-Asissted Group Investigation Cooperative learning model. The research instrument used was a test of learning outcomes in the form of posttest questions. Hypothesis testing shows the value of Fcount > Ftable which means H0 is rejected, thus it can be concluded that there is a significant difference in average learning outcomes. Furthermore, based on further testing with the BNT test, It was obtained: The learning outcomes of students that applied the Geogebra-Asissted Cooperative learning model were not significantly different from the class that applied the Group Investigation type of Cooperative learning model. The learning outcomes of students that applied the Geogebra-Asissted Cooperative learning model were significantly different from the class that applied the Direct Instruction model. The learning outcomes of students that applied the Group Investigation type of Cooperative learning model were significantly different from the class that applied the Direct Instruction learning model.Keywords: Geometry Learning Outcomes, Group Investigation, Direct Instruction, Geogebra